2017
DOI: 10.1080/15622975.2016.1273552
|View full text |Cite
|
Sign up to set email alerts
|

Reduced astrocyte density underlying brain volume reduction in activity-based anorexia rats

Abstract: Volumetric brain changes in ABA animals mirror those in human AN patients. These alterations are associated with a reduction of GFAP-positive astrocytes as well as GFAP expression. Reduced astrocyte functioning could help explain neuronal dysfunctions leading to symptoms of rigidity and impaired learning. Astrocyte loss could constitute a new research target for understanding and treating semi-starvation and AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 55 publications
8
46
0
1
Order By: Relevance
“…Accordingly, animals with the largest inhibitory contacts ran the least during food access and had the most prominent FAA. 44 Overall cortex and corpus callosum volumes in the brains of ABA rats have also been shown to be reduced by 6% and 9%, respectively, 45 compared to controls, in line with grey and white matter reductions reported in acute AN. 46 The acute phase of ABA (ie the first 3 days) is also associated with a reduction in hippocampal cell proliferation 47 and ABA rats demonstrate alterations in dendritic branching 48 and maturation of hippocampal neurones, 49 cellular substrates that could contribute to the reduced hippocampal volumes seen in acutely ill AN patients.…”
Section: Brain Structure and Function In Abasupporting
confidence: 71%
“…Accordingly, animals with the largest inhibitory contacts ran the least during food access and had the most prominent FAA. 44 Overall cortex and corpus callosum volumes in the brains of ABA rats have also been shown to be reduced by 6% and 9%, respectively, 45 compared to controls, in line with grey and white matter reductions reported in acute AN. 46 The acute phase of ABA (ie the first 3 days) is also associated with a reduction in hippocampal cell proliferation 47 and ABA rats demonstrate alterations in dendritic branching 48 and maturation of hippocampal neurones, 49 cellular substrates that could contribute to the reduced hippocampal volumes seen in acutely ill AN patients.…”
Section: Brain Structure and Function In Abasupporting
confidence: 71%
“…New studies detected astrocyte loss in both GM and WM of activity‐based anorexia rats after semi‐starvation. This could help explain neuronal dysfunctions leading to symptoms of rigidity and impaired learning in AN (Frintrop et al, ; Seitz, Konrad, & Herpertz‐Dahlmann, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration/rehydration and osmotic effects are believed to be unlikely to produce brain volume alterations of such extent (Bernardoni et al, 2016;King et al, 2015;Yau et al, 2013). Seitz et al (2016) This could help explain neuronal dysfunctions leading to symptoms of rigidity and impaired learning in AN (Frintrop et al, 2018;Seitz, Konrad, & Herpertz-Dahlmann, 2017).…”
Section: Global Segment Volumesmentioning
confidence: 99%
“…Atypical anorexia nervosa is defined as anorexia nervosa that does not meet full diagnostic criteria, typically those individuals are not below a certain weight threshold, such as the 5th percentile for age adjusted BMI. Two studies by Olivo et al found normal gray and white matter in adolescents with atypical anorexia nervosa, further supporting the hypothesis that body weight is directly related to brain structure, although the mechanism is not yet well understood (Frintrop et al, 2017;Olivo et al, 2018;Olivo et al, 2019).…”
Section: Research On Brain Structurementioning
confidence: 84%